Personality Traits and Entrepreneurial Intentions: Financial Risk-Taking as Mediator - Salameh, Anas A.; Akhtar, Hameeda; Gul, Rani; Omar, Abdullah Bin; Hanif, Sobia (Frontiers in Psychology, 2022)
The interaction between environment and individual personality determine career. Over the past decades, the role of personality traits in explaining entrepreneurship cannot get much attention of researchers. To fill this gap, the current study aims to investigate the effect of personality traits (extraversion, openness to experience, conscientiousness, neuroticism and agreeableness) on the entrepreneurial intentions along with the mediating role of financial risk taking. Sample size consist of 500 students of business and management of different universities of Pakistan, out of which 466 useable questionnaires were collected and analyzed. The results of the study are consistent with conventional wisdom as explored by past studies. In line with past studies and proposed hypothesis, we found that extraversion, openness to experience both have a positive association with financial risk taking, whereas neuroticism, conscientiousness and agreeableness have negative association with financial risk taking. Results also revealed that there is positive association between financial risk taking and entrepreneurial intentions, however, financial risk taking did not mediate the relationship between agreeableness and entrepreneurial intentions.